Somatic Embryogenesis in Iberian Grapevine (Vitis vinifera) Cultivars Using Carpels as Initial Explants: Protocol Establishment and Histological Evaluation - Cardoso, Hélia (2019)
Trincadeira and Aragonez are two important grapevine cultivars in the Iberian Peninsula, used for high quality red wines production. Both cultivars are strongly affected by fungal diseases, with consequent high loses on plant productivity and fruit quality. A successful protocol for plant regeneration via somatic embryogenesis (SE) was established for both cultivars allowing further plant improvement based on gene transfer technology. Several factors were evaluated during the three different phases which characterize an SE plant regeneration protocol. The culture room temperature during the induction phase, a parameter usually accepted as standard by most researchers, proved in these trials to significantly affect the embryo induction rates. Concerning embryo conversion, it was specially affected by the embryo developmental stage, by the intensity and duration of the chilling treatment and by the supplementation of conversion culture medium with activated charcoal. The responses obtained, both for induction and conversion, proved to be highly genotype dependent. Calli structure, as well as embryo integrity, was histologically observed, allowing to characterize embryonic and non-embryonic masses and to identify abnormalities on embryo development.